英王的教室(讓我教你們炮製一條好知識),
http://hk.knowledge.yahoo.com/question/?qid=7006050200471的回答並不適用於這條數學題,就算如何修改都不適用。http://hk.knowledge.yahoo.com/question/?qid=7006050200471之所以要咁做,就是因為A, B, C, D是該四件物件的價錢,而物件的價錢只能是正數,頂多是兩位小數,佢之所以要咁做是可以理解的。
但係睇番呢題,這四個數的角色只是未知數,並不是該四件物件的價錢,所以並不存在正數、兩位小數等限制。這題只是一條聯立方程,不是應用題,故無須兼顧實用性。好似你的做法,就算數值上做得有幾啱都好,但是概念上你已經完全錯哂!!!
其實這題要咁做先至啱:
Let the four unknowns be a, b, c and d,
Then
╭
_│a + b + c + d = 7.11
│abcd = 7.11
╰
Let a = p , b = q , c = r ,for all p, q, r in C\{0}
Then d = 7.11 – p – q – r
∴The solution set of a + b + c + d = 7.11 is {(p , q , r , 7.11 – p – q – r) , p , q , r belongs to real number}
Put the solution set into abcd = 7.11 :
pqr(7.11 – p – q – r) = 7.11
7.11pqr – p²qr – pq²r – pqr² = 7.11
pqr² + p²qr + pq²r – 7.11pqr + 7.11 = 0
pqr² + (p²q + pq² – 7.11pq)r + 7.11 = 0
r = [– (p²q + pq² – 7.11pq) ± √[(– (p²q + pq² – 7.11pq))² – 4pq × 7.11]]/(2pq)
= [7.11pq – p²q – pq² ± √[(p²q + pq² – 7.11pq)² – 28.44pq]]/(2pq)
∴d = 7.11 – p – q – [7.11pq – p²q – pq² ± √[(p²q + pq² – 7.11pq)² – 28.44pq]]/(2pq)
= [14.11pq – 2p²q – 2pq² – 7.11pq + p²q + pq² (– or +) √[(p²q + pq² – 7.11pq)² – 28.44pq]]/(2pq)
= [7.11pq – p²q – pq² (– or +) √[(p²q + pq² – 7.11pq)² – 28.44pq]]/(2pq)
Note: p and q are independent of each other, i.e. they may be equal or unequal
Therefore, there are infinitely many solution of a, b, c and d.
Taking p = 1 and q = 2 as a case, we have
a = 1
b = 2
c = [7.11 × 1 × 2 – 1² × 2 – 1 × 2² ± √[(1² × 2 + 1 × 2² – 7.11 × 1 × 2)² – 28.44 × 1 × 2]]/(2 × 1 × 2)
= [8.22 ± √[(– 8.22)² – 56.88]]/4
= (8.22 ± √10.6844)/4
= (411/50 ± √(26711/2500))/4
= (411 ± √26711)/200
d = (411 (– or +) √26711)/200
╭
│a = 1
∴_│b = 2
│c = (411 ± √26711)/200
│d = (411 (– or +) √26711)/200
╰
In fact the general expression is
╭
│a = p
_│b = q
│c = [7.11pq – p²q – pq² ± √[(p²q + pq² – 7.11pq)² – 28.44pq]]/(2pq)
│d = [7.11pq – p²q – pq² (– or +) √[(p²q + pq² – 7.11pq)² – 28.44pq]]/(2pq)
╰
for all p, q in C\{0}
Hence the four unknowns are p, q, [7.11pq – p²q – pq² + √[(p²q + pq² – 7.11pq)² – 28.44pq]]/(2pq) and [7.11pq – p²q – pq² – √[(p²q + pq² – 7.11pq)² – 28.44pq]]/(2pq) respectively, for all p, q in C\{0}.